2019
DOI: 10.1177/0145445519878670
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of Randomized Controlled Trials of the Good Behavior Game

Abstract: The Good Behavior Game (GBG) is widely recognized as an evidence-based intervention that reinforces prosocial behaviors and discourages disruptive behaviors among students in the classroom setting. The current meta-analysis synthesized randomized controlled trials of the GBG to examine its impact on proximal student outcomes across seven studies representing 4,700 children. Although recent reviews focusing on single-case studies of the GBG have reported moderate to large treatment effects, our results were qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…As a secondary effect of the interdependent group contingency, Smith et al (2019) found reduced social withdrawal of target children as rated by their peers in four studies. Similarly, all children with ASD in this study increased their selections of the peer option over the alone option after the interdependent group contingency was introduced.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As a secondary effect of the interdependent group contingency, Smith et al (2019) found reduced social withdrawal of target children as rated by their peers in four studies. Similarly, all children with ASD in this study increased their selections of the peer option over the alone option after the interdependent group contingency was introduced.…”
Section: Discussionmentioning
confidence: 96%
“…Besides its direct effects on the target behavior, the interdependent group contingency is also known to produce collateral benefits. In a meta-analysis by Smith et al (2019), they found reduced shyness and social withdrawal of children as rated by their peers in four studies. Smith et al hypothesized that the reduced social withdrawal might be due, in part, to the social interaction and cooperation among children as promoted by the group contingency.…”
Section: Reciprocal Social Conversation Framework For Children With Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…A fifteenth RCT based in the United States reports on the impact of the GBG in the context of an afterschool program ( Smith et al, 2018 ). Collectively, these trials have provided robust evidence that the intervention leads to statistically significant changes in a range of salient outcomes, including conduct problems and peer relations, with intent-to-treat (ITT) effect sizes typically in the g = 0.10–0.20 range ( Smith et al, 2021 ). This evidence is broadly consistent with intervention effect sizes reported in meta-analyses of a range of universal behavior management approaches ( Korpershoek et al, 2016 ) and school-based preventive interventions more generally ( Tanner-Smith, Durlak, & Marx, 2018 ).…”
Section: Introductionmentioning
confidence: 99%